DIVERSIFIKASI USAHA DAN MANAJEMEN LABA DENGAN PENDEKATAN CONDITIONAL REVENUE MODEL - Haryanto, Matthew; Lina, Lina (Jurnal Akuntansi, 2017)
Generally, go public companies are belong to large-scale companies or even international ones. Mostly those companies have more than one business divisions, therefore the financial reports might be published in more than one segments. According to Financial Accounting Standard 5, the company financial reports can be distinguished between geographical segments and operating segments. This study aims to give the empirical evidence about the influence of the business diversification towards earnings management. The amount of the geography segments and the operating segments are used as proxy to represent the business diversification. The earnings management is measured by conditional revenue model. The data is collected from the company annual reports by accessing through Indonesia Stock Exchange website for period 2011-2013. The sampling method used is purposive sampling. Data analysis used multiple linear regressions. The result of the study shows that the geography segments have no influence on the earnings management, meanwhile the operating segments have positive influence on earnings management.